Bezpieczne formy aktywności fizycznej dla kobiet w ciąży = Secure forms of physical activity for pregnant women - Katarzyna Urtnowska; Irena Bułatowicz; Grzegorz Ludwikowski; Walery Zukow (Kazimierz Wielki University, 2016)
Urtnowska Katarzyna, Bułatowicz Irena, Ludwikowski Grzegorz, Zukow Walery. Bezpieczne formy aktywności fizycznej dla kobiet w ciąży = Secure forms of physical activity for pregnant women. Journal of Education, Health and Sport. 2016;6(5):291-297. eISSN 2391-8306. DOI http://dx.doi.org/10.5281/zenodo.51894 http://ojs.ukw.edu.pl/index.php/johs/article/view/3526     The journal has had 7 points in Ministry of Science and Higher Education parametric evaluation. Part B item 755 (23.12.2015). 755 Journal of Education, Health and Sport eISSN 2391-8306 7 © The Author (s) 2016; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 25.04.2016. Revised 10.05.2016. Accepted: 18.05.2016.   Bezpieczne formy aktywności fizycznej dla kobiet w ciąży   Secure forms of physical activity for pregnant women     Katarzyna Urtnowska1, Irena Bułatowicz2, Grzegorz Ludwikowski3, Walery Zukow4     1Uczestnik studiów dokotranckich z zakresu Nauk o Zdrowiu; Zakład Medycyny Rozdrodu i Andrologii, Collegium Medicum im. L. Rydygiera w Bydgoszczy Uniwersytet Mikołaja Kopernika w Toruniu 2Katedra Fizjoterapii - Zakład Fizjoterapii Klinicznej, Collegium Medicum im. L. Rydygiera w Bydgoszczy Uniwersytet Mikołaja Kopernika w Toruniu 3Zakład Medycyny Rozdrodu i Andrologii, Collegium Medicum im. L. Rydygiera w Bydgoszczy Uniwersytet Mikołaja Kopernika w Toruniu 4Wydział Kultury Fizycznej, Zdrowia i Turystyki, Uniwersytet Kazimierza Wielkiego w Bydgoszczy           mgr Katarzyna Urtnowska1, dr n. med. Irena Bułatowicz2, dr hab. n. med. Grzegorz Ludwikowski3, dr hab. Walery Zukow4 1Uczestnik studiów dokotranckich z zakresu Nauk o Zdrowiu; Zakład Medycyny Rozdrodu i Andrologii, Collegium Medicum im. L. Rydygiera w Bydgoszczy Uniwersytet Mikołaja Kopernika w Toruniu 2Katedra Fizjoterapii - Zakład Fizjoterapii Klinicznej, Collegium Medicum im. L. Rydygiera w Bydgoszczy Uniwersytet Mikołaja Kopernika w Toruniu 3Zakład Medycyny Rozdrodu i Andrologii, Collegium Medicum im. L. Rydygiera w Bydgoszczy Uniwersytet Mikołaja Kopernika w Toruniu 4Wydział Kultury Fizycznej, Zdrowia i Turystyki, Uniwersytet Kazimierza Wielkiego w Bydgoszczy           Słowa kluczowe: ciąża, aktywność fizyczna, sport. Keywords: pregnancy, physical activity, sport.           Streszczenie Kobieta spodziewać się dziecka w dzisiejszych czasach ma wiele możliwości podjęcia bezpiecznej formy aktywności fizycznej. Z odrobiną racjonalnego podejścia może kontynuować uprawianie ulubionego sportu, lub uczestniczyć w zajęciach przygotowanych specjalnie dla ciężarnych. Aktywność fizyczna uprawiana regularnie w trakcie ciąży jest kluczowym czynnikiem wpływającym na zdrowie i samopoczucie matki. Ćwiczenia wpływają korzystnie na stan zdrowia poprzez zmniejszenie dolegliwości bólowych kręgosłupa, ogólną poprawę lub brak pogorszenia sprawności fizycznej, zapobieganie nadmiernemu przyrostowi masy ciała i poprawę samopoczucia ciężarnej. Dodatkowym, a zarazem najważniejszym efektem jest zwiększenie wydolności fizycznej niezbędnej do porodu siłami natury i skrócenie czasu jego przebiegu oraz czasu regeneracji organizmu w połogu, a co za tym idzie, szybszy powrót do formy sprzed ciąży.     Abstract A women expect a child a child today has a lot of possibilities for secure forms of physical activity. With a bit of rational approach may continue playing your favorite sport, or participate in activities prepared especially for pregnant women. Physical activity practiced regularly during pregnancy is a key factor in the health and well-being of the mother. Exercise influence on health status by reducing the pain of the spine, improve general or no deterioration of physical fitness, prevention of excessive weight gain and improving well being pregnant. Extra and, at the same time, the most important effect is to increase the physical capacity required for the labor forces of nature and shorten its course and recovery time of the organism in the postpartum period, and hence a faster return to pre-pregnancy form.